Heyndrickxia coagulans strain SANK70258 suppresses symptoms of upper respiratory tract infection via immune modulation: a randomized, double-blind, placebo-controlled, parallel-group, comparative study - Aida, Masanori; Togawa, Naoyuki; Mizuyama, Kazuyuki; Aoki, Yoshinori; Suehiro, Shouhei; Sakamoto, Akiho; Uchida, Noriyoshi; Yamada, Ryouichi (Frontiers in Immunology, 2024)
Probiotic consumption strongly influences local intestinal immunity and systemic immune status. Heyndrickxia coagulans strain SANK70258 (HC) is a spore-forming lactic acid bacterium that has immunostimulatory properties on peripheral tissues.However, few reports have examined the detailed effectiveness of HC on human immune function and its mechanism of action. Therefore, we conducted a randomized, double-blind, placebo-controlled, parallel-group study to comprehensively evaluate the effects of HC on immunostimulatory capacity, upper respiratory tract infection (URTI) symptoms, and changes in intestinal organic-acid composition. Results of a questionnaire survey of URTI symptoms showed that runny nose, nasal congestion, sneezing, and sore throat scores as well as the cumulative number of days of these symptoms were significantly lower in the HC group than in the placebo group during the study period. Furthermore, the salivary secretory immunoglobulin A (sIgA) concentration was significantly higher, and the natural killer (NK) cell activity tended to be higher in the HC group than in the placebo group. In addition, we performed an exposure culture assay of inactivated influenza virus on peripheral blood mononuclear cells (PBMCs) isolated from the blood of participants in the HC and placebo groups.Gene-expression analysis in PBMCs after culture completion showed that IFNα and TLR7 expression levels were significantly higher in the HC group than in the placebo group. In addition, the expression levels of CD304 tended to be higher in the HC group than in the placebo group. On the other hand, the HC group showed a significantly higher increase in the intestinal butyrate concentration than the placebo group. HC intake also significantly suppressed levels of IL-6 and TNFα produced by PBMCs after exposure to inactivated influenza virus. Collectively, these results suggest that HC activated plasmacytoid dendritic cells expressing TLR7 and CD304 and strongly induced IFNα production, subsequently activating NK cells and increasing sIgA levels, and induced anti-inflammatory effects via increased intestinal butyrate levels. These changes may contribute to the acquisition of host resistance to viral infection and URTI prevention.